2022
DOI: 10.3389/fphys.2022.866792
|View full text |Cite
|
Sign up to set email alerts
|

Exercise as an Aging Mimetic: A New Perspective on the Mechanisms Behind Exercise as Preventive Medicine Against Age-Related Chronic Disease

Abstract: Age-related chronic diseases are among the most common causes of mortality and account for a majority of global disease burden. Preventative lifestyle behaviors, such as regular exercise, play a critical role in attenuating chronic disease burden. However, the exact mechanism behind exercise as a form of preventative medicine remains poorly defined. Interestingly, many of the physiological responses to exercise are comparable to aging. This paper explores an overarching hypothesis that exercise protects agains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 196 publications
0
1
0
Order By: Relevance
“…High levels of physical exercise can enhance the function of vascular endothelial cells, promote the release of pro-inflammatory and anti-inflammatory cytokines, reduce the incidence of viral infections, and effectively decrease the risk of suicide [ 14 , 15 ]. A study indicates that physical exercise plays a significant role in the prevention and treatment of many chronic or age-related diseases (such as musculoskeletal diseases, metabolic diseases, and cardiovascular diseases) [ 16 ]. Further studies have indicated that intrinsic motivation for exercise plays a critical role in determining mental health [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…High levels of physical exercise can enhance the function of vascular endothelial cells, promote the release of pro-inflammatory and anti-inflammatory cytokines, reduce the incidence of viral infections, and effectively decrease the risk of suicide [ 14 , 15 ]. A study indicates that physical exercise plays a significant role in the prevention and treatment of many chronic or age-related diseases (such as musculoskeletal diseases, metabolic diseases, and cardiovascular diseases) [ 16 ]. Further studies have indicated that intrinsic motivation for exercise plays a critical role in determining mental health [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%